이기종 디바이스 지원을 위한 크로스 플랫폼 기반 XR 콘텐츠 개발 - 장희진(Heejin Jang); 이성희(Sunghee Lee); 신정훈(Jung Hun Shin); 이승민(Seungmin Lee); 김민아(Min Ah Kim); 남덕윤(Dukyun Nam) (디지털콘텐츠학회논문지, 2023)
확장 현실 (XR) 기술 분야에서 다자간 협업을 위한 이기종 XR 디바이스 간 호환성 및 상호운용성 지원 문제는 여전히 도전적인과제이다. 이기종 사용자 간 상호작용을 지원하기 위해 XR 콘텐츠 개발 시 XR 디바이스들의 다양한 입력 장치와 플랫폼을 고려해야 하지만, 이를 위한 크로스 플랫폼 설계 및 XR 콘텐츠 개발에 관한 모범 사례는 찾아보기 어렵다. 본 논문에서는 OpenXR 표준과XR 개발 도구들을 활용해 크로스 플랫폼 개발 환경을 구축하고 4종의 이기종 디바이스를 이용해 협업을 지원하는 XR 콘텐츠를개발하였다. 또한 XR 콘텐츠와 MRTK 기반의 크로스 플랫폼 개발에 관해 소개하고, 실험을 통해 이기종 XR 디바이스 사용자들이손동작, 터치스크린 등 다양한 입력 도구들을 활용하여 가상 객체 및 다른 사용자와 상호작용할 수 있음을 실증하였다. Supporting multi-user collaboration across diverse heterogeneous XR devices remains challenging in extended reality technology,primarily because of compatibility and interoperability issues. XR content creators are tasked with considering various input devices andplatforms across XR devices to facilitate user interactions. However, it is difficult to determine the practices for cross-platform designand XR content development. In this paper, we set up a cross-platform development environment based on OpenXR and XRdevelopment tools and develop XR collaboration content designed to support interactions across four different XR devices. Furthermore, this paper introduces XR content and discusses cross-platform development based on the Mixed Reality Toolkit. Theexperiment empirically demonstrates that users of diverse XR devices can interact with virtual objects and other users using variousinput methods such as gestures and touchscreens. KCI Citation Count: 0